2013
DOI: 10.1186/1471-2334-13-75
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of the benefits of enhanced cross-protection against cervical cancer and prevention of genital warts in the cost-effectiveness analysis of human papillomavirus vaccination in the Netherlands

Abstract: BackgroundInfection with HPV 16 and 18, the major causative agents of cervical cancer, can be prevented through vaccination with a bivalent or quadrivalent vaccine. Both vaccines provide cross-protection against HPV-types not included in the vaccines. In particular, the bivalent vaccine provides additional protection against HPV 31, 33, and 45 and the quadrivalent vaccine against HPV31. The quadrivalent vaccine additionally protects against low-risk HPV type 6 and 11, responsible for most cases of genital wart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…Most of the studies [8] examined the cost-effectiveness of HPV vaccination for young girls aged 10-12 [14][15][16][17]19,30,32,33]. Almost half of the studies [4] investigated the influence of adding HPV vaccination to cervical screening only [14][15][16][17].…”
Section: Strategies/comparator and Study Questionsmentioning
confidence: 97%
See 3 more Smart Citations
“…Most of the studies [8] examined the cost-effectiveness of HPV vaccination for young girls aged 10-12 [14][15][16][17]19,30,32,33]. Almost half of the studies [4] investigated the influence of adding HPV vaccination to cervical screening only [14][15][16][17].…”
Section: Strategies/comparator and Study Questionsmentioning
confidence: 97%
“…Almost half of the studies [4] investigated the influence of adding HPV vaccination to cervical screening only [14][15][16][17]. Moreover, two studies explored various strategies, either the addition of specific screening techniques to vaccination [16,19] or explicit comparisons between the quadri-and bivalent vaccine [32]. Coupe et al also explored the influence of various screening strategies (HPV DNA vs cytology and 4-7 screenings during specific age periods) and cross-protection in addition to direct protection [19,30].…”
Section: Strategies/comparator and Study Questionsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, some level of cross-protection against nonvaccine HPV types has been demonstrated for the prophylactic vaccines Gardasil and Cervarix (7)(8)(9)(10)(11)(12)(13)(14). In the phase III randomized, doubleblinded clinical trial examining the efficacy of Cervarix, Paavonen et al observed vaccine efficacy not only against cervical intraepithelial neoplasias of grade 2 and worse (CIN2ϩ) associated with HPV-16 and -18 but also against CIN2ϩ associated with HPV-31, -33, and -45 (11).…”
mentioning
confidence: 99%